Best kept secret [large type] - Archer, Jeffrey, 1940- (Archer, Jeffrey, 1940- Clifton chronicles, 2013)
Harry Clifton, now a bestselling novelist, his wife Emma, their son Sebastian, and orphaned Jessica make a new life for themselves. But Emma's brother Giles' fiancée may be after his fortune and title. And Sebastian, though bright, has a hard time resisting temptation. It all comes to a head when a new villain is uncovered, a face from the past with grudges against both Harry and Giles.